2005
DOI: 10.1016/j.cattod.2005.07.049
|View full text |Cite
|
Sign up to set email alerts
|

Nopol synthesis over Sn-MCM-41 and Sn-kenyaite catalysts

Abstract: Several methods were used to prepare Sn loaded kenyaite and MCM-41 silicates: ion exchange, incipient wetness impregnation and chemical vapor deposition. Catalysts were evaluated for nopol synthesis by the Prins condensation of b-pinene and paraformaldehyde. The resulting catalysts were characterized by elemental analysis, TGA, XRD, FTIR, BET surface area and UV-vis. Kenyaite samples modified with Sn by ion exchange were more resistant to leaching than those modified by chemical vapor deposition (CVD), while S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 16 publications
0
16
0
Order By: Relevance
“…Sn-incorporation enhanced the catalytic activity. The highest catalytic activity is observed for the sample prepared by method D. It has been reported that weak and medium acid sites of Sn (IV) cations are responsible for the Prins condensation reaction [37,38]. The TPD profiles given in Fig.…”
Section: Synthesis Of Nopol By Prins Condensationmentioning
confidence: 75%
See 1 more Smart Citation
“…Sn-incorporation enhanced the catalytic activity. The highest catalytic activity is observed for the sample prepared by method D. It has been reported that weak and medium acid sites of Sn (IV) cations are responsible for the Prins condensation reaction [37,38]. The TPD profiles given in Fig.…”
Section: Synthesis Of Nopol By Prins Condensationmentioning
confidence: 75%
“…Recently, Montes de Correa et al [37] have reported the synthesis of nopol over Sn-MCM-41 molecular sieves using toluene as a solvent at 363 K. About 90% yield of nopol was obtained using a catalyst in which Sn was grafted by chemical vapor deposition (CVD) over MCM-41. Sn-kenyaite catalysts prepared by CVD method reported high nopol selectivity, but the b-pinene conversion was around 50% [38]. More recently, a mesoporous iron phosphate catalyst has been reported for the selective synthesis of nopol at 353 K in acetonitrile solvent [39].…”
Section: Introductionmentioning
confidence: 98%
“…Al, and Sn) MCM-41 mesoporous molecular sieves, [21][22][23][24][25][26] SnCl 4 grafted onto MCM-41, [27] ZnCl 2 -impregnated Montmorillonite, [28] and Sn-SBA-15. [29] However, the doping of metals into mesoporous silica does not produce single-site catalysts and, as a result of their amorphous natures, metal-doped mesoporous materials are not stable enough for industrial purposes usually because of the leaching of the active phase.…”
Section: Introductionmentioning
confidence: 99%
“…Hydrochloric acid, alkyl-substituted aluminum chlorides (Williams et al, 2002), SnCl 4 (Andersen et al, 1985), InCl 3 (Yadav et al, 2003), and heteropolyacids (Li et al, 2004) are typically used to catalyze Prins reaction in homogeneous systems. Several heterogeneous catalytic systems have also been reported for Prins condensation of β-pinene with formaldehyde, including mesoporous iron phosphate (Pillai and Sahle-Demessie, 2004), Fe–Zn double cyanide (Patil et al, 2007), metal supported (Zn-, Al- and Sn-) MCM-41 mesoporous molecular sieves (de Villa and Alarcon, 2002; Corma and Renz, 2007; Alarcon et al, 2010; Selvaraj and Sinha, 2010), SnCl 4 grafted on MCM-41 (de Villa et al, 2005), ZnCl 2 impregnated on Montmorillonite (Yadav and Jasra, 2006), and Sn-SBA-15 (Selvaraj and Choe, 2010). However, doping of metals into mesoporous silica does not produce single site catalysts and due to the amorphous nature, metal-doped mesoporous materials are not stable enough due to a leaching of the active phase.…”
Section: Introductionmentioning
confidence: 99%